Psychometric properties of the World Health Organization WHOQOL-AGE Scale in Singapore. - Lee, Rachael Zhi Yi; Yang, Winson Fu Zun; Mahendran, Rathi; Suárez, Lidia (European Journal of Ageing, 2024)
WHOQOL-AGE is a promising quality of life (QOL) tool that has not been fully validated in Asia. The present study aimed to verify its factor structure and psychometric properties among community-dwelling older adults in Singapore. This study was cross-sectional and used data (N = 593) from the Community Health and Intergenerational study that interviewed older adults between 2018 and 2021. Confirmatory factor analysis (CFA) was used to examine the factor structure of the WHOQOL-AGE, and Cronbach’s alpha coefficients were employed to examine internal consistency. Spearman’s rho correlations coefficients between WHOQOL-AGE and other related scales (Satisfaction with Life and the Friendship) examined convergent validity. A Pearson’s correlation coefficient between WHOQOL-AGE and compassion scale examined discriminant validity. An independent t test was used to demonstrate known-groups validity, examining differences in QOL scores between individuals with and without chronic medical conditions. Findings supported a bifactor model with more satisfactory goodness-of-fit indices than the original two-factor model and the two-correlated factor model. WHOQOL-AGE showed adequate internal consistency (Cronbach’s alpha coefficients >.70). Good convergent validity was demonstrated by moderate-to-large correlations between WHOQOL-AGE and satisfaction with life (r =.54) as well as social connectedness (r =.33). Discriminant validity was shown by low correlations between WHOQOL-AGE and compassion (r =.19). Findings also indicated good known-groups validity (p < 0.01). The WHOQOL-AGE showed promising psychometric properties using an Asian convenience sample and can be useful in large-scale studies or busy clinical settings.